Effective Application of Dynamic Visual Elements in Web Design - Xu, Ao (Transactions on Social Science, Education and Humanities Research, 2023)
Through the study of the category and composition of graphic elements in web design, this paper discusses the psychological response, information guidance and auxiliary communication role of graphic elements in the network space. This paper introduces a method of representation of visual elements in dynamic scenes based on attention sequence. A method of constructing observation vector based on multiple visual elements is proposed. Secondly, the text graphics and music graphics of information graphics in web interface design are designed. Aiming at the information graph and interaction design in the network environment, the concept of information graph is put forward. And the emotion expression of the information graph is designed in detail. The network interface proposed in this paper has achieved good effect in visual expression and obtained a high degree of user satisfaction through an example.